Reconstruction of gene innovation associated with major evolutionary transitions in the kingdom Fungi - Baojun Wu; Weilong Hao; Murray P. Cox (BMC Biology, 2022)
Abstract Background Fungi exhibit astonishing diversity with multiple major phenotypic transitions over the kingdom’s evolutionary history. As part of this process, fungi developed hyphae, adapted to land environments (terrestrialization), and innovated their sexual structures. These changes also helped fungi establish ecological relationships with other organisms (animals and plants), but the genomic basis of these changes remains largely unknown. Results By systematically analyzing 304 genomes from all major fungal groups, together with a broad range of eukaryotic outgroups, we have identified 188 novel orthogroups associated with major changes during the evolution of fungi. Functional annotations suggest that many of these orthogroups were involved in the formation of key trait innovations in extant fungi and are functionally connected. These innovations include components for cell wall formation, functioning of the spindle pole body, polarisome formation, hyphal growth, and mating group signaling. Innovation of mitochondria-localized proteins occurred widely during fungal transitions, indicating their previously unrecognized importance. We also find that prokaryote-derived horizontal gene transfer provided a small source of evolutionary novelty with such genes involved in key metabolic pathways. Conclusions The overall picture is one of a relatively small number of novel genes appearing at major evolutionary transitions in the phylogeny of fungi, with most arising de novo and horizontal gene transfer providing only a small additional source of evolutionary novelty. Our findings contribute to an increasingly detailed portrait of the gene families that define fungal phyla and underpin core features of extant fungi.